2006
DOI: 10.1038/sj.emboj.7601098
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cγ/diacylglycerol-dependent activation of β2-chimaerin restricts EGF-induced Rac signaling

Abstract: Although receptor-mediated regulation of small G-proteins and the cytoskeleton is intensively studied, the mechanisms for attenuation of these signals are poorly understood. In this study, we have identified the Rac-GAP b2-chimaerin as an effector of the epidermal growth factor receptor (EGFR) via coupling to phospholipase Cc (PLCc) and generation of the lipid second messenger diacylglycerol (DAG). EGF redistributes b2-chimaerin to promote its association with the small GTPase Rac1 at the plasma membrane, as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
80
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(98 citation statements)
references
References 35 publications
11
80
1
6
Order By: Relevance
“…Furthermore, we could not see any translocation of α2-chimaerin upon treatment of cells with PMA although, in this case, β2-chimaerin did show an enrichment in the cellular membranes of Jurkat cells. This behavior is in contrast to previous results in this GAP family in other cell types [34,35,37]. Several observations indicate that the lack of regulation of chimaerin by DAG in Jurkat cells is not an experimental artifact.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Furthermore, we could not see any translocation of α2-chimaerin upon treatment of cells with PMA although, in this case, β2-chimaerin did show an enrichment in the cellular membranes of Jurkat cells. This behavior is in contrast to previous results in this GAP family in other cell types [34,35,37]. Several observations indicate that the lack of regulation of chimaerin by DAG in Jurkat cells is not an experimental artifact.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous works have shown that the upregulation of the activity of chimaerins during signal transduction occurs concurrently with their shuttling from the cytosol to either the Golgi apparatus or the plasma membrane. This translocation occurs through the binding of the chimaerin C1 domain to DAG and, in the case of the Golgi apparatus, on the additional binding of β2-chimaerin to the Golgi-localized Timp21-I protein [34,35,37]. To study whether a similar regulation occurred in T-cells, we monitored the changes in the subcellular localization of EGFP-tagged α2-and β□-chimaerin upon the treatment of Jurkat cells with anti-CD3 antibodies for 5 min.…”
Section: Chimaerin Proteins Do Not Translocate To the Plasma Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Another possible effector of PLCc in RBL-2H3 cells is b2-chimaerin, which is a diacylglycerol-stimulated GTPaseactivating protein (GAP) specific for Rac [44]. A recent study in HeLa cells in fact has shown that activation of b-chimaerin inhibits EGF stimulation of Rac [45]. This mechanism could explain the effects of PLCc on Rac in mast cells.…”
Section: Discussionmentioning
confidence: 95%
“…DAG is a lipid second messenger produced at cell membranes from phosphatidylinositol 4,5-bisphosphate by members of the phospholipase C (PLC) family in response to a wide variety of stimuli. The C1 domain allows chimaerins to translocate to membranes in response to DAG signaling (6,16) and is likely to anchor them in close proximity to activated Rac.It is becoming clear that the SH2 domain is central to the regulation of ␣2-and ␤2-chimaerin activity, as under unstimulated conditions it folds over and occludes the C1 and GAP domains, auto-inhibiting the whole molecule (17-19). However, because ␣1-chimaerin lacks this SH2 domain, it is not clear how its activity is regulated.…”
mentioning
confidence: 99%